Charakterystyka form prawnych commercial papers emitowanych w Polsce - Iwanienko, Izabela (The Essence and the Classification of Forms of Legal Emitted Commercial Papers in Poland, 2007)
The aim of the present article is a presentation of performance of commercial papers as a rational source of capital gains financial market for contractors. The paper also discusses forms of indebted legal short-term papers on the Polish, in particular papers emitted in support of the Law on bills of exchange, Code civilian as well as the Law of bonds
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 125-134